Presence and Persistence of Salmonella in Water: The Impact on Microbial Quality of Water and Food Safety - Liu, Huanli; Whitehouse, Chris A.; Li, Baoguang (Frontiers in Public Health, 2018)
Salmonella ranks high among the pathogens causing foodborne disease outbreaks. According to the Centers for Disease Control and Prevention, Salmonella contributed to about 53.4% of all foodborne disease outbreaks from 2006 to 2017, and approximately 32.7% of these foodborne Salmonella outbreaks were associated with consumption of produce. Trace-back investigations have suggested that irrigation water may be a source of Salmonella contamination of produce and a vehicle for transmission. Presence and persistence of Salmonella have been reported in surface waters such as rivers, lakes, and ponds, while ground water in general offers better microbial quality for irrigation. To date, culture methods are still the gold standard for detection, isolation and identification of Salmonella in foods and water. In addition to culture, other methods for the detection of Salmonella in water include most probable number, immunoassay, and PCR. The U.S. Food and Drug Administration issued the Produce Safety Rule (PSR) in January 2013 based on the Food Safety Modernization Act, which calls for more efforts toward enhancing and improving approaches for the prevention of foodborne outbreaks. In the PSR, agricultural water is defined as water used for in a way that is intended to, or likely to, contact covered produce, such as spray, wash, or irrigation. In this review, we will discuss mechanisms Salmonella uses to persist in the aquatic environment, particularly irrigation water, to better understand the impact on the microbial quality of water and food safety due to the presence of Salmonella in the water environment.